Synthesis of CaCO3@C yolk-shell particles for CO2 adsorption - Boyjoo, Yashveersingh; Merigot, K.; Lamonier, J.; Pareek, Vishnu; Tade, Moses; Liu, Jian (Royal Society of Chemistry, 2015)
We report the synthesis of CaCO3@C yolk–shell particles with a microporous carbon shell through a selective etching method. The CaCO3@C exhibits an enhanced CO2 adsorption, relative to the porous CaCO3 nanoparticles or the porous carbon shell, with a capacity of 19.30 cm3 STP g−1 (0.86 mmol g−1 or 31.64 cm3 STP cm−3 sorbent) under ambient conditions (23 ± 1 °C and 1 atm CO2).